2013
DOI: 10.1016/j.otsr.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular microarchitecture in established osteoporosis: Relationship between vertebrae, distal radius and calcaneus by X-ray imaging texture analysis

Abstract: IV retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Similarly, bone thickness at the anterior area was significantly reduced only at the right condyles. It has been previously -13 -shown that significant correlations exist between bone volume and texture parameters (in particular GLN) measured on X-ray images [35][36][37][38][39] . In this clinical condition, GLN could reflect a trabecular bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, bone thickness at the anterior area was significantly reduced only at the right condyles. It has been previously -13 -shown that significant correlations exist between bone volume and texture parameters (in particular GLN) measured on X-ray images [35][36][37][38][39] . In this clinical condition, GLN could reflect a trabecular bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the results of this examination can be strongly biased by degenerative changes in facet joints and even by aortic calcification. [5][6][7][8] Being useful in the workup of a variety of spinal conditions, including degenerative diseases, computed tomography (CT) is also capable of accurately defining bone radiodensity using Hounsfield units (HU). Even though it has been reported that BMD has a strong relationship with radiodensity measured in HU, application of those parameters for implant failure prediction remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…F. Mallard et al . 9 performed texture analysis on the X-ray images of spine, distal radius and calcaneus, realized the early detection of changes in the microarchitecture of bones, and demonstrated the values of texture analysis for preventing and treating osteoporosis. Muthu Subash Kavitha et al .…”
Section: Introductionmentioning
confidence: 99%